The burden of sialorrhoea in chronic neurological conditions: current treatment options and the role of incobotulinumtoxinA (Xeomin®). (November 2019) - Morgante, Francesca; Bavikatte, Ganesh; Anwar, Fahim; Mohamed, Biju
Sialorrhoea is a frequent symptom of neurological diseases (e.g. Parkinson's disease, motor neuron disease, cerebral palsy, and stroke) and is defined as excessive saliva accumulation leading to unintentional loss of saliva from the mouth. Sialorrhoea increases the overall burden on the patient and their caregivers, the impact of which can be both physical and psychosocial. Treatments for sialorrhoea range from lifestyle and behavioural guidance, to medications, surgery or radiation. Nonpharmacological interventions include advice on posture, swallowing control, cough management, dietary changes, eating and drinking techniques, and behavioural modification; however, these conservative measures may be ineffective for people with progressive neurological conditions. The pharmacological treatment of sialorrhoea is challenging because medications licensed for this purpose are limited, but treatments can include anticholinergic drugs and botulinum toxins. Surgical treatment of sialorrhoea is typically reserved as a last resort for patients. IncobotulinumtoxinA (Xeomin®) is the first botulinum toxin type A to receive US and UK marketing authorization for the symptomatic treatment of chronic sialorrhoea due to neurological disorders in adults. In this review, we discuss and compare the frequency and method of administration, location of treatment delivery, approximate annual costs and main side effects of botulinum toxin and different anticholinergic drugs. Management of patients with chronic neurological conditions requires input from multiple specialist teams and thus a multidisciplinary team (MDT) approach is considered fundamental to ensure that care is consistent and tailored to patients' needs. To ensure that adult patients with neurological conditions receive the best care and sialorrhoea is well managed, we suggest a potential clinical care pathway for sialorrhoea with a MDT approach, which healthcare professionals could aspire to.